Sharia Based Financial Management in the Mushroom Farming Women's Business Group in Taman Sari Village - Novi Yanti Sandra Dewi; Ahmad Hulaimi; Syaharuddin Syaharuddin (ITB AAS INDONESIA Surakarta, 2023)
The mushroom farming women who are members of the mushroom farming women's group in Taman Sari Village use most of the income derived from the mushroom business for consumption. This income depends on the number of baglogs of mushrooms, the more the number of baglogs, the greater the income. However, the number of baglog owned by this mushroom farmer woman has not increased from year to year and there are no mushroom derivative products. This study aims to determine the financial management of the mushroom business of women's mushroom farming groups so that the business can develop, avoid losses that may occur in the future, and earn the pleasure of Allah. This study uses qualitative methods with phenomenological analysis tools. The research location is limited to Taman Sari Village to obtain specific findings. The informant is a Muslim female mushroom farmer who is married and also works as a stone crusher. Mushroom farming women have not recorded the financial transactions of the mushroom business and only rely on memory. They have not separated business finances from family finances, and have not divided the money from selling mushrooms in a ratio that is in accordance with Islamic concepts.